Structural characteristic of Na2O-P2O5-GeO2 glass systems - Sahar, Mohd Rahim; Hussein, A. Wahab M.A.; Hussin, R (Science Direct, 2007)
Phosphate glasses based on xNa2O0.5P2O5(0.5-x)GeO2 (0.0 x 0.5) mol%, were prepared and their structures were characterized by magic angle spinning (MAS) nuclear magnetic resonance (NMR), Raman and IR spectroscopy techniques. It was found that the phosphate network of these glasses is composed of middle (Q2) and branching (Q3) phosphate tetrahedra, whereas germanium part in the network is composed of three- or four-membered GeO4 tetrahedral rings. It was also found that the germanium tetrahedral are randomly connected to either Q2 or Q3 phosphate units in the network. The glass network, especially the Q2 units can be modified by the presence of Na ions. This modification is primarily associated with the phosphate. It is found that these glasses behave as if they are formed from a solution of GeO2 and sodium–phosphate glass with various GeO4 units and the Q2 and Q3 phosphate units randomly distributed in the network.